Case Report: Lumbar spondylolisthesis with unilateral pedicle cleft and contralateral spondylolysis: a report of two cases and literature review - Chang, Sheng; Wang, Yu; Liu, Yong; Wang, Chao (Frontiers in Surgery, 2024)
The causes of pedicle cleft include congenital dysplasia a n d stress fractures, both of which are rare conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Secondary lumbar spondylolisthesis with combined unilateral pedicle cleft and contralateral spondylolysis is extremely rare and can be easily misdiagnosed. We report two cases with such conditions but from different causes and discuss the diagnostic and therapeutic features in the context of the literature review.Case one was a 58-year-old female with a stress fracture change at the left L5 pedicle. Case two was a 47-year-old female with a pedicle cleft due to hypoplasia of the left L5 pedicle. Both patients had a combined contralateral spondylolysis and Meyerding grade one lumbar spondylolisthesis, while neither had a clear history of lumbar trauma. After initial conservative treatments failed, both patients underwent a single-segment posterior lumbar interbody fusion with bilateral pedicle screw fixation. Both patients were followed up for more than one year postoperatively with clinical symptom relief and bony fusion at the pedicle cleft suggested by a CT scan.Lumbar spondylolisthesis with unilateral pedicle cleft and contralateral spondylolysis is rarely reported and can be clinically misdiagnosed as simple spondylolisthesis with bilateral spondylolysis. There is no widely-accepted surgical option for patients for whom conservative treatment has failed.Our experience suggests that good clinical results may be achieved by single segment posterior interbody fusion and bilateral pedicle screw fixation. Precise screw placement into the deficient pedicle and sufficient exiting nerve decompression are prerequisites for the success of this surgical option.